Complex Interactions Between Human Immunodeficiency Virus Type-1, Sex, and Osteopontin Influence Viral Replication and Leukocyte Proportions in Tissues - Mahmud, Farina J.; Greif, Elizabeth; Boucher, Thomas; Metcalf Pate, Kelly A.; Lyons, Claire; Carlson, Bess; Brown, Amanda M. (Frontiers in Virology, 2021)
It is becoming increasingly clear that several aspects of HIV pathogenesis differ by sex, a variable known to influence the extent and breadth of immune responses in health and disease that should be included in research designs. Our prior studies using cultured human macrophages showed that the cytokine-like factor osteopontin (OPN) stimulates HIV replication. To test whether OPN has the same positive impact at the level of tissues, we used a humanized mice model of low-level chronic HIV infection and inhibition of OPN RNA and protein expression with targeted aptamers. Necropsy was performed more than four months later. Interestingly, while HIV viral load in plasma showed no significant differences, reduced expression of OPN in the spleen, lung, and liver differentially affected the tissue burden of HIV RNA, as well as the proportion of leukocytes in female and male mice. The findings collectively demonstrate the potential for complex interactions between host factors like OPN and sex to influence different facets of HIV tissue-level pathogenesis.